Wie mobil sind die Menschen wirklich?: Empirische Perspektiven zur Diskussion um Kirche zwischen Ortsgemeinde und Regionalisierung - Roleder, Felix (Pastoraltheologie, 2020)
The question about how community-centered or regionally-oriented the church should be has long been a topic of discussion. This article seeks to offer a new perspective by looking, what had not been done, at representative data drawn from everyday practices. The results show that a great majority of people spend their free time socially outside the area of their local parish. On the other hand, a significant minority of people do maintain a local orientation. For future church work, the possibility of a local-regional model allowing for differentiation of groups might be considered that does justice to people’s varying needs.